1999
DOI: 10.1038/sj.ejhg.5200247
|View full text |Cite
|
Sign up to set email alerts
|

Hearing impairment and neurological dysfunction associated with a mutation in the mitochondrial tRNASer(UCN) gene

Abstract: We studied a large Dutch family with maternally inherited, progressive, sensorineural hearing loss in 27 patients. Only in a single family member was the hearing loss accompanied by neurological symptoms including ataxia and dysarthria. DNA analysis of the mitochondrial genome revealed the insertion of a C at nucleotide position 7472 in the tRNA Ser(UCN) gene (7472insC mutation). We determined the percentage of mutant DNA (heteroplasmy) in blood from all family members, and found no correlation between hearing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(38 citation statements)
references
References 17 publications
0
38
0
Order By: Relevance
“…Of these, four non-syndromic deafness-associated mutations: A7445G [Reid et al, 1994;Fischel-Ghodsian et al, 1995], 7472insC [Verhoeven et al, 1999;Jacobs et al, 2005], T7510C [Hutchin et al, 2000;del Castillo et al, 2002] and T7511C [Sue et al, 1999;Li et al, 2005a], have been identified in the tRNA Ser(UCN) gene. The C1494T mutation in the highly conserved decoding site of the 12S rRNA has been associated with both aminoglycoside-induced and nonsyndromic hearing loss in a large Chinese family [Zhao et al, 2004a;Zhao et al, 2005].…”
Section: Introductionmentioning
confidence: 99%
“…Of these, four non-syndromic deafness-associated mutations: A7445G [Reid et al, 1994;Fischel-Ghodsian et al, 1995], 7472insC [Verhoeven et al, 1999;Jacobs et al, 2005], T7510C [Hutchin et al, 2000;del Castillo et al, 2002] and T7511C [Sue et al, 1999;Li et al, 2005a], have been identified in the tRNA Ser(UCN) gene. The C1494T mutation in the highly conserved decoding site of the 12S rRNA has been associated with both aminoglycoside-induced and nonsyndromic hearing loss in a large Chinese family [Zhao et al, 2004a;Zhao et al, 2005].…”
Section: Introductionmentioning
confidence: 99%
“…Several mtDNA point mutations have been reported in families with maternally inherited NSSHI; the A1555G mutation in the 12S rRNA gene, which also causes hypersensitivity to aminoglycosides 1,2 and four mutations affecting the tRNASer (UCN) gene -A7445G, 7472insC, T7510C and T7511C. [3][4][5][6][7] The frequency of these mutations in the general population has yet to be determined. Both the A1555G and A7445G mutations have been reported in different ethnic populations raising the possibility that such mutations are more common causes of hearing loss than initially thought.…”
mentioning
confidence: 99%
“…In the Dutch family, the hearing loss is sensorineural progressive with onset in early adulthood, and only a single family member with hearing loss showed accompanying neurological symptoms. The mutation is heteroplasmic, although most individuals have over 90% of abnormal mitochondrial chromosomes in the tissues examined [46]. The 7472insC mutation seems to occur multiple times in the European population than others.…”
Section: Mitochondrial Trna Mutations Associated With Nonsyndromic Hementioning
confidence: 86%
“…Most individuals carrying this mutation had progressive SNHL, and some of them were accompanied by a widespread neurological disease including ataxia, dysarthria, and myoclonic seizures. This mutation was later found in a large Dutch family [46] and in several sporadic subjects with nonsyndromic hearing loss [47]. In the Dutch family, the hearing loss is sensorineural progressive with onset in early adulthood, and only a single family member with hearing loss showed accompanying neurological symptoms.…”
Section: Mitochondrial Trna Mutations Associated With Nonsyndromic Hementioning
confidence: 95%
See 1 more Smart Citation